2018
DOI: 10.1111/codi.13958
|View full text |Cite
|
Sign up to set email alerts
|

A novel three‐dimensional printed guiding device for electrode implantation of sacral neuromodulation

Abstract: Aim The aim was to test the feasibility of a novel threedimensional (3D) printed guiding device for electrode implantation of sacral neuromodulation (SNM).Method A 3D printed guiding device for electrode implantation was customized to patients' anatomy of the sacral region. Liquid photopolymer was selected as the printing material. The details of the device designation and prototype building are described. The guiding device was used in two patients who underwent SNM for intractable constipation. Details of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…By means of a 3D printing technique, Taverner et al successfully performed SNM to treat pain in a patient with a failed epidural puncture and achieved satisfactory results. In China, Cui applied 3D printing to SNM to achieve the expected results and suggested that this technique is simple to use even for a beginner, but its efficacy requires further observation. We have extensively discussed the 3D printing technique and design with Cui to create a ready‐to‐use and reassembled 3D template.…”
Section: Discussionmentioning
confidence: 99%
“…By means of a 3D printing technique, Taverner et al successfully performed SNM to treat pain in a patient with a failed epidural puncture and achieved satisfactory results. In China, Cui applied 3D printing to SNM to achieve the expected results and suggested that this technique is simple to use even for a beginner, but its efficacy requires further observation. We have extensively discussed the 3D printing technique and design with Cui to create a ready‐to‐use and reassembled 3D template.…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al . created a 3D printed device that helped guide electrode insertion in sacral neuromodulation. The principal clinical advantage of this model is in allowing precise entry of the test needle into the target foramen at a consistent angle of 60° in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…However, identifying the opening of the sacral foramen is still a challenge for less experienced surgeons, especially if the patient has unusual sacral anatomy [22]. Cui et al [13] created a 3D printed device that helped guide electrode insertion in sacral neuromodulation. The principal clinical advantage of this model is in allowing precise entry of the test needle into the target foramen at a consistent angle of 60°in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations